Investigation on fatigue behavior of single SnAgCu/SnPb solder joint by rapid thermal cycling. Issue 2 (7th April 2015) - Chen, Jibing; Yin, Yanfang; Ye, Jianping; Wu, Yiping
Abstract : Purpose: – The purpose of this paper is to investigate the thermal fatigue behavior of a single Sn-3.0Ag-0.5Cu (SAC) lead-free and 63Sn-37Pb (SnPb) solder joint treated by rapidly alternating heating and cooling cycles. Design/methodology/approach: – With the application of electromagnetic-induced heating, the specimen was heated and cooled, controlled with a system that uses a fuzzy logic algorithm. The microstructure and morphology of the interface between the solder ball and Cu substrate was observed using scanning electron microscopy. The intermetallic compounds and the solder bump surface were analyzed by energy-dispersive X-ray spectroscopy and X-ray diffraction, respectively. Findings: – The experimental results showed that rapid thermal cycling had an evident influence on the surface and interfacial microstructure of a single solder joint. The experiment revealed that microcracks originate and propagate on the superficial oxide of the solder bump after rapid thermal cycling. Originality/value: – Analysis, based on finite element modeling and metal thermal fatigue mechanism, determined that the rimous cracks can be explained by the heat deformation theory and the function of temperature distribution in materials physics.